A taxonomic revision of the genus Dimeria (Poaceae: Panicoideae) in Thailand - Teerawatananon, Atchara; Boontia, Veeraya; Chantarasuwan, Bhanumas; Hodkinson, Trevor R.; Sungkaew, Sarawood (Phytotaxa, 2014)
A taxonomic treatment of the genus Dimeria in Thailand is presented. Seven species are recognised and a new locality record is reported. Nomenclature, description and illustration are provided for each species. Four lectotypes are designated.